2009
DOI: 10.2174/156652409787847245
|View full text |Cite
|
Sign up to set email alerts
|

Riboregulators and Metabolic Disorders: Getting Closer Towards Understanding the Pathogenesis of Diabetes Mellitus?

Abstract: Type 2 Diabetes occurs as a result of defects in insulin secretion and its function. Although mechanisms of disease are not fully elucidated, it is recognized that a progressive decline in insulin secretory capacity is responsible for its occurrence and natural course. Metabolic syndrome, known to be a precursor of Type 2 diabetes, is characterized by a constellation of vascular risk factors, with obesity playing a central role. Obesity contributes to impaired insulin function and abnormal glucose metabolism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Among more than 10000 miRNAs identified in 115 species so far [Sanger miRNA database release 14.0 http://www.mirbase.org/], only a handful have been linked to glucose metabolism and metabolic disorders [30]. Among them, miR-375 that is abundantly expressed in pancreatic and beta cells, negatively regulates glucose-stimulated insulin secretion via myotrophin ( Mtpn ) inhibition [31], [32].…”
Section: Introductionmentioning
confidence: 99%
“…Among more than 10000 miRNAs identified in 115 species so far [Sanger miRNA database release 14.0 http://www.mirbase.org/], only a handful have been linked to glucose metabolism and metabolic disorders [30]. Among them, miR-375 that is abundantly expressed in pancreatic and beta cells, negatively regulates glucose-stimulated insulin secretion via myotrophin ( Mtpn ) inhibition [31], [32].…”
Section: Introductionmentioning
confidence: 99%
“…Binding to regulatory sites of target mRNA, miRNAs modify their expression by translational repression or target mRNA degradation to cause decreased protein production [25]. MiRNAs are involved in the regulation of insulin secretion and response and in glucose homeostasis [26]. Moreover, they are required in adipocyte differentiation and fatty acid synthesis in hepatocytes [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, it has been demonstrated that extracellular vesicles circulating in human plasma, which are a mixture of microparticles, exosomes, and other structures such as apoptotic bodies, contain miRNAs that can be considered as a novel class of signaling molecules mediating intercellular communication. 14 Some of these circulating miRNAs have been linked to glucose metabolism, 15 while others, such as miR-144 , miR-146a , miR-150 , miR-182 , miR-192 , mir-29a , miR-30d , and miR-320 , seem to participate in the regulation of insulin signaling. 16 , 17 There are others, too, such as miR-375 , 18 , 19 , 20 , 21 miR-96 , 22 and miR-124a , 23 which have been associated with the development of T2DM and may also be involved in its progression.…”
Section: Introductionmentioning
confidence: 99%